Teenage Motorcycle Gang Behavior in Medan: A Review of Freud's Personality Theory - Handayani, Tri Quari; Sariyanti, Lilis; Ariani, Desti (Riwayat: Educational Journal of History and Humanities, 2025)
The rise of teenage motorcycle gangs in Medan represents a significant social and psychological issue, marked by patterns of violence, delinquency, and identity crises. This study aims to explore the deviant behavior of adolescent gang members through the lens of Sigmund Freuds structural personality theory, particularly examining the roles of the id, ego, and superego, and the influence of childhood trauma on personality development. A qualitative-descriptive method was used to collect in-depth insights from selected informants, including active and former gang members, school counselors, community leaders, and law enforcement personnel. Data were gathered through limited observation, in-depth interviews, and document analysis. Thematic analysis following Braun and Clarke (2006) was applied, with themes constructed around key Freudian concepts. Findings indicate that the dominance of the id, weakened ego regulation, and an underdeveloped superego contribute to impulsive, aggressive, and morally detached behaviors among gang members. Early trauma, such as emotional neglect and exposure to domestic violence, significantly impairs personality development. In many cases, the gang provides a psychological refuge and an alternative moral structure, substituting familial support. Defense mechanisms such as rationalization and projection are commonly used by adolescents to justify their violent acts. The study concludes that understanding gang behavior from a psychoanalytic perspective provides a deeper comprehension of the psychological roots of violence. It also highlights the need for early psychosocial intervention, family-based support, and structured therapeutic programs focused on rebuilding ego strength and moral reasoning.